Consumer’s Preference and Awareness: Comparative Analysis between Conventional and Islamic Ijarah Auto Financing in Pakistan - Chhapra, Imran Umer; Ahmed, Afzal; Rehan, Raja; Hussain, Farasat (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2018)
A healthy banking industry plays a vital role in the economic stability, and banks success depends on its products. Therefore, this study aims at cognizing the consumer’s preference and awareness of Islamic Ijarah over the conventional lease in Pakistan. This research used regression as tools of analysis. The findings indicate that convenience is the prime determinant for preference of Ijarah over the lease. Moreover, all other factors except religion also support in the motivate selection of Islamic banking products. Therefore, it can be concluded that in Pakistan, religion is not the only fact motivates individuals to prefer Ijarah. Based on findings, it is recommended to relevant stakeholders to create more awareness among masses about Ijarah and to further ease out policies in order to harness optimum benefit.DOI: 10.15408/aiq.v10i2.7106